Penerapan Konseling Behavioral dengan Teknik Penokohan (Modelling) untuk Meningkatkan Motivasi Belajar Siswa Kelas VII A SMPK 2 Harapan Tahun Pelajaran 2019/2020 - I Dewa Ayu Eka Purba Dharma Tari; Kadek Suhardita; I Putu Karpika; I Ketut Sapta; Ni Luh Rosita Diantari (JKI (Jurnal Konseling Indonesia), 2020)
The purpose of this study was to determine the effectiveness of Behavioral Counseling with modeling techniques to increase learning motivation of class VII A SMPK 2 Harapan students in the 2019/2020 academic year. This research is a classroom action research conducted in two cycles. Research subjects in this study were 36 students. Through the observation questionnaire assessment conducted there were 5 students who have low learning motivation. The results of this study indicate that from 19.14% to 35.71% with an initial data score of 43.8%, an increase of 30.34% to 57% in the low category. Furthermore, the results of the second cycle (II) action, it is clear that there is an increase in the learning motivation of class VII A students of SMPK 2 Harapan for the 2019/2020 academic year from 22.03% to 36.36% with an initial data score of 57%, an increase of 29.95%. to 74% in the high category. This proves that behavioral counseling with modeling techniques is effective for increasing learning motivation of grade VII A students of SMK 2 Harapan for the 2019/2020 academic year.